2022
DOI: 10.3390/pr10071310
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hydrokinetic Turbine Backwater Prediction Model for Inland Flow through Validated CFD Models

Abstract: Hydrokinetic turbine deployment in inland water reticulation systems such as irrigation canals has potential for future renewable energy development. Although research and development analysing the hydrodynamic effects of these turbines in tidal applications has been carried out, inland canal system applications with spatial constraints leading to possible blockage and backwater effects resulting from turbine deployment have not been considered. Some attempts have been made to develop backwater models, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Furthermore, studies about change in guide vane air foil on the flow characteristics of draft tube for improvement of energy recovery, vibrations intensity, stable operation of turbine, design methods of multiphase pumps for hydrodynamic and structural points of view, etc. have been performed widely in the past (Benavides-Morán, Rodríguez-Jaime and Laín, 2022; Niebuhr et al, 2022;Peng et al, 2022).They conclude that the power coefficient is affected by presence of free surface. Similarly, authors in (Lopez Mejia et al, 2021) propose practise guidelines for CFD simulations in turbines studying the performance standard of vertical axis and horizontal axis turbines and those in (Xiong, Deng and Chen, 2021) study about flapping motion in tail edge which is found to present a better stability for turbine.…”
Section: 2mentioning
confidence: 96%
“…Furthermore, studies about change in guide vane air foil on the flow characteristics of draft tube for improvement of energy recovery, vibrations intensity, stable operation of turbine, design methods of multiphase pumps for hydrodynamic and structural points of view, etc. have been performed widely in the past (Benavides-Morán, Rodríguez-Jaime and Laín, 2022; Niebuhr et al, 2022;Peng et al, 2022).They conclude that the power coefficient is affected by presence of free surface. Similarly, authors in (Lopez Mejia et al, 2021) propose practise guidelines for CFD simulations in turbines studying the performance standard of vertical axis and horizontal axis turbines and those in (Xiong, Deng and Chen, 2021) study about flapping motion in tail edge which is found to present a better stability for turbine.…”
Section: 2mentioning
confidence: 96%
“…Modelling and simulation of horizontal-and vertical-axis turbines for hydrokinetic applications [10][11][12][13][14].…”
mentioning
confidence: 99%
“…All of these contributions use CFD in different problems, ranging from vertical-axis turbines to horizontal-axis turbines, but all have the common characteristic of the inclusion of more details (either geometrical or physical) in the simulation. For example, Niebuhr et al proposed a simplified model for the calculation of a small horizontal-axis turbine that includes backwater effects [10]. The model uses the data generated from CFD simulations that include not only the presence of the walls (channel flow), but also the free surface using a multiphase model.…”
mentioning
confidence: 99%